2013
DOI: 10.1016/j.atherosclerosis.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

T-wave axis deviation, metabolic syndrome and estimated cardiovascular risk – In men and women of the MOLI-SANI study

Abstract: Title: T-wave axis deviation, metabolic syndrome and estimated cardiovascular risk in men and women of the MOLI-SANI Study Methods: 11,143 women (54±11 years) and 9,742 men (55±11 years) were analysed from the Molisani cohort, randomly recruited from the general population. MetS was defined using the ATPIII criteria. T-wave axis deviation was measured from the standard 12-lead resting electrocardiogram.CVD risk in ten years was estimated by the CUORE score.Results: 29% of men and 27% of women with MetS showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…As a test with a high prediction value, it can be used to predict the chance of CVD development. 14 It is worth noting that the majority of studies have investigated the effects of MetS only on one or few markers from the patients’ electrocardiograms, such as aortic stiffness, 15 T-wave axis, 16 , 17 resting heart rate, 18 QT interval, ST segment, and Q-wave, 14 or assessed the effect of only one component of the MetS, such as blood glucose, 19 , 20 obesity, 21 and/or abdominal adiposity 22 on the majority of ECG markers. This suggests that there are few similar studies in the world and no similar study in Iran as comprehensive as the present study.…”
Section: Introductionmentioning
confidence: 99%
“…As a test with a high prediction value, it can be used to predict the chance of CVD development. 14 It is worth noting that the majority of studies have investigated the effects of MetS only on one or few markers from the patients’ electrocardiograms, such as aortic stiffness, 15 T-wave axis, 16 , 17 resting heart rate, 18 QT interval, ST segment, and Q-wave, 14 or assessed the effect of only one component of the MetS, such as blood glucose, 19 , 20 obesity, 21 and/or abdominal adiposity 22 on the majority of ECG markers. This suggests that there are few similar studies in the world and no similar study in Iran as comprehensive as the present study.…”
Section: Introductionmentioning
confidence: 99%
“…There was a nearly two-fold increased risk of coronary heart disease death, and an approximately 50% increased risk of incident coronary artery disease and all-cause mortality, for those with marked T wave axis deviation [17]. Moreover, T wave axis deviation is correlated with metabolic syndrome, low-grade systemic inflammation, and left ventricular hypertrophy in patient with diabetes mellitus or pregnancy [1821]. ECG-ViEW II contains 41,258 patients with an abnormal T wave axis and provides an opportunity to evaluate the correlation of many diseases with the T wave axis parameter.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of digital electrocardiography, currently standard in most Countries, has further widened the diagnostic capabilities of this technique for pharmacological and epidemiological studies as well as for a preclinical diagnosis of cardiac disease (33). T wave axis seems to be an ECG measure which is useful for better stratifying individual risk, as compared and in addition with the traditional use of cardiovascular risk factors (14). A better stratification with an inexpensive tool could allow, in the next future, a more focused and effective preventive intervention in individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently speculated that obesity and hypertension could have a relevant role in the pathogenesis of abnormal T-axis (13). In addition, later studies showed that abnormal T-wave axis shift is independently associated with the metabolic syndrome (14), suggesting that a careful electrocardiogram (ECG) recording should be made in persons with metabolic syndrome in order to make an early detection of abnormal T-axis in clinical practice.…”
Section: The Multiple Risk Factormentioning
confidence: 99%
See 1 more Smart Citation